Transformasi Pembelajaran Berbasis Learning Management System melalui Pendampingan E-Learning di Madrasah Aliyah Raudhatul Muhajirin - Utomo, Pradita Eko Prasetyo; Siburian, Jodion; Octavia, Ade; Suryahartati, Dwi; Ilhami, Mohammad; Suprayogi, Dawam (Fakultas Sains dan Teknologi, Universitas Jambi, 2026)
The digital transformation of education requires schools to adopt learning technologies that enhance the effectiveness and quality of instructional processes. However, MAS Raudhatul Muhajirin still faces limitations in utilizing Learning Management Systems (LMS), resulting in conventional teaching and administrative practices. This community service program aims to improve the digital competence of teachers and students through mentoring and training in Moodle-based LMS development. The method employed a participatory and collaborative approach, including needs assessment, system development, training, and intensive mentoring integrated within the MBKM thematic community service program. The results indicate that the development of four main digital instruments, namely the e-learning platform, school website, profile video, and 360° virtual tour, has improved access to digital learning, administrative efficiency, and users’ pedagogical and digital literacy skills. Despite challenges related to infrastructure and administrative readiness, the program contributed positively to the transformation of learning into a more adaptive and technology-based system. These findings highlight that the success of educational technology implementation depends not only on the system itself but also on human resource readiness and sustainable support.